The Lending Interest Rates in the Microfinance Sector: Searching for its Determinants - Cotler, Pablo (2013)
Using data from 1299 microfinance institutions (MFIs) in 84 countries and following different approaches, it was found the lending interest rate is determined by the funding cost, the loan size, and the efficiency level of MFIs. With respect to competition, results are mixed. Only in Asia is a negative correlation between competition and lending interest rates detected. For other subsamples, it was found the competition is more likely to be negatively correlated with the size of loans.